Implementation of Entrepreneurship in Teachers’ Colleges Implications for Teacher Educators and Captains of Industry in Zimbabwe - Nani, Gwendoline, V.; Mpofu, M. (Zimbabwe Journal of Science & Technology, 2015)
The study was conducted to find out whether selected teachers’ colleges are equipping educators with Entrepreneurship education so as to enable them to impart relevant knowledge and skills to the learners. A case study design was adopted which used focus group interviews and semi-structured face to face interviews for data collection. The researchers chose Bulawayo Metropolitan Province because of the diversity of its institutions. Lecturers, students and captains of industry were purposively selected because of their in depth knowledge on the issue being studied. Findings revealed that Entrepreneurship is not taught as a stand-alone subject but is infused in National and Strategic Studies (NASS) and Commercial subjects. Further revelations were that the selected institutions did not have specialists to teach Entrepreneurship and captains of industry were not consulted in the development of programmes. The study concluded that teachers’ colleges in Bulawayo Metropolitan Province lack the capacity to teach practising teachers Entrepreneurship. Recommendations are that Entrepreneurship as a course be introduced and taught by specialists who should consult captains of industry so that relevant knowledge and skills on successful and sustainable businesses are imparted.
Article
Keywords: Entrepreneurship; implementation; implications; subject specialists; entrepreneurship education